Effect of anaerobic phases length on denitrifying dephosphatation biocenosis – a case study of IFAS-MBSBBR - Anna Gnida; Monika Żubrowska-Sudoł; Katarzyna Sytek-Szmeichel; Jolanta Podedworna; Joanna Surmacz-Górska; Dorota Marciocha (BMC Microbiology, 2020)
Abstract Background The study aimed to evaluate the influence of the duration times of anaerobic phases on the bacterial biocenosis characterisation while denitrifying dephosphatation in the Integrated Fixed-Film Activated Sludge – Moving-Bed Sequencing Batch Biofilm Reactor (IFAS-MBSBBR). The experiment was conducted in a laboratory model. The study consisted of four series, which differed in terms of the ratio of the anaerobic phases. duration concerning the overall reaction time in the cycle. The anaerobic phases covered from 18 to 30% of the whole cycle duration. During the reactor performance that took 9 months, the influent and effluent were monitored by analysis of COD, TKN, NH4-N, NO2-N, NO3-N, TP, PO4-P, pH, alkalinity and the phosphorus uptake batch tests. Characterisation of the activated sludge and the biofilm biocenosis was based on fluorescent in situ hybridisation (identification of PAO and GAO) and the denaturing gradient gel electrophoresis patterns. Results The organic compounds removal was high (more than 95.7%) independently of cycle configuration. The best efficiency for nitrogen (91.1%) and phosphorus (98.8%) removal was achieved for the 30% share of the anaerobic phases in the reaction time. Denitrifying PAO (DPAO) covered more than 90% of PAO in the biofilm and usually around 70% of PAO in the activated sludge. A substantial part of the polyphosphate accumulating organisms (PAO) community were Actinobacteria. The denitrifying dephosphatation activity was performed mainly by Accumulibacter phosphatis. Conclusions High nutrient removal efficiencies may be obtained in IFAS-MBSBBR using the denitrifying dephosphatation process. It was found that the length of anaerobic phases influenced denitrification and the biological phosphorus removal. The extension of the anaerobic phases duration time in the reaction time caused an increase in the percentage share of denitrifying PAO (DPAO) in PAO. The biocenosis of the biofilm and the activated sludge reveal different species patterns and domination of the EBPR community.